PENGARUH MODEL PBL BERBANTUAN MEDIA PEMBELAJARAN MONOPOLI IPA TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF SISWA PADA MATERI BAGIAN TUBUH TUMBUHAN BESERTA FUNGSINYA - Lisa Septi Ardila; Rosmiati, Rosmiati; Triman Juniarso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was driven by the challenge of low student performance in understanding plant body parts and their functions, along with their limited ability to engage in reflective thinking. The primary goal of this research was to examine the impact of Science Monopoly as a learning tool on students' reflective thinking skills and to evaluate their responses after engaging with this media in a fourth-grade science class.Science Monopoly was designed to foster an interactive, enjoyable, and immersive learning environment, making complex concepts more accessible to students. The findings revealed a remarkable improvement in reflective thinking skills. In the first experimental class, the average pretest score was 55.19, which rose significantly to 89.04 in the posttest. Similarly, the second experimental class saw an increase from an average pretest score of 50.19 to 77.04. The N-Gain score reached 1.00 for the first class and 0.54 for the second. Furthermore, hypothesis testing yielded a significance value (Sig. 2-tailed) of 0.000, confirming that the Science Monopoly learning media effectively enhances students' reflective thinking abilities.Given these results, Science Monopoly has demonstrated its potential as a valuable educational tool that significantly contributes to students' cognitive development. Its implementation is strongly recommended for broader use in science education, particularly in subjects that require a deeper conceptual grasp.